Tunnel Bone Grafting in Revision Anterior Cruciate Ligament Reconstruction Cruciate Ligament Reconstruction. Issue 7 (30th July 2018) - Owens, Brett D.; Group, Mars
Objectives: Bone grafting of lytic or malpositioned tunnels may be required in ACL revision reconstructive surgery. Little is known of the characteristics of these patients and the impact of this practice on the results following revision ACL reconstruction (rACLR). The purpose of this study was to report the differences in preoperative characteristics, surgical assessment, and 2-year outcomes for rACLR patients undergoing tunnel bone grafting procedures. Methods: 1205 patients who underwent rACLR were enrolled in the Multicenter ACL Revision Study (MARS) consortium between 2006 and 2011, comprising the prospective cohort. Two-year questionnaire follow-up was obtained on 989 (82%), while telephone follow-up was obtained on 1112 (92%). Subjects undergoing previous or concurrent bone grafting of ACL tunnels were compared with subjects without tunnel grafting. Group characteristics were compared using chi-squared and ANOVA statistical analyses. Results: At total of 158 subjects (13%) underwent tunnel grafting procedures compared to 1, 047 who did not. Of these, 95 underwent prior staged bone grafting and 63 underwent concomitant bone grafting. Femoral bone grafting was performed on 31 subjects, tibial grafting in 39, and combined grafting in 88. Significant differences were noted in baseline patient reported outcomes (KOOS sports/recreation, KOOS QOL, and Marx activity) favoring the control group. Significant differences were noted in the number of prior ACL reconstructions, prior graft type, prior femoral fixation method, prior femoral and tibial tunnel locations between the two groups. Significant differences were also noted in the current choice of ACL revision reconstruction technique including graft selection, method of femoral tunnel drilling, femoral fixation, tibial fixation and aperture assessment. Both femoral and tibial bone quality was deemed to be abnormal in 20% of revision surgeries in the bone graft group, compared with 6 and 7% in control group (both p<0.001). Two-year patient reported outcomes were inferior in the bone graft group (KOOS sports/recreation, KOOS QOL, and Marx activity). Conclusion: Tunnel bone grafting was performed in 13% of ACL revision patients. These patients had inferior baseline and 2-year patient reported outcomes and activity levels compared to patients not undergoing bone grafting.